2016
DOI: 10.1061/(asce)be.1943-5592.0000773
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Evaluation of Polyurethane-Based GFRP Sandwich Bridge Deck Panels with Polyurethane Foam Core

Abstract: This paper presents the evaluation of an innovative low-cost small-scale prototype deck panel under monotonic and fatigue bending. This new system introduces a trapezoidal-shaped polyurethane foam core with a thermoset polyurethane resin that has a longer pot life to facilitate the infusion process. The proposed panel exhibited a higher structural performance in terms of flexural stiffness, strength, and shear stiffness. The panels consist of two glass fiber-reinforced polymer (GFRP) facings with webs of bidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…As expected, the loadstrain curves presented a non-linear evolution of strain at the compression and tension side of the specimens. The load-strain evolution may be expected based on the behavior of the individual constituent materials comprising a sandwich structure [47]. The aluminium skin and EPS core used in this research were ductile in nature and typically respond in a non-linear fashion.…”
Section: Comparison Of Load-strain Behaviourmentioning
confidence: 99%
“…As expected, the loadstrain curves presented a non-linear evolution of strain at the compression and tension side of the specimens. The load-strain evolution may be expected based on the behavior of the individual constituent materials comprising a sandwich structure [47]. The aluminium skin and EPS core used in this research were ductile in nature and typically respond in a non-linear fashion.…”
Section: Comparison Of Load-strain Behaviourmentioning
confidence: 99%
“…In addition, Abaqus 6.11 FE code was used to conduct numerical simulations of the developed panels. The results were verified and compared with the experimental results gathered from four-point bending tests conducted on the sandwich panels (Tuwair et al 2015b;Tuwair et al 2016). The verified FE model was then used to conduct a parametric study to investigate the effects of the stiffness of the top facesheet fiber layers, the mass density of the polyurethane foam, and the existence of an overlay on top of the deck on the deflection, initial stiffness, and strength of the GFRP panels.…”
Section: Introductionmentioning
confidence: 58%
“…They found that the simplified I-beam modeling approach was the most computationally efficient method for studying the overall performance of honeycomb sandwich panels. Tuwair et al (2015b) recently developed a new multicellular FRP bridge panel ( Fig. 1) in which the initial production costs and manufacturing difficulties were reduced while the system performance was improved.…”
Section: Introductionmentioning
confidence: 99%
“…eir test results showed that specimens with trapezoid foam core had highest load carrying capacity under flexural loads and compression, due to the presence of shear layer. A similar approach of trapezoidalshaped polyurethane foam core was considered by Tuwair et al [11], who found that the shear webs contributed significantly to delaying the delamination of the skins from the core. e numerical analysis of Mostafa et al [12] showed that inserting shear keys between the GFRP facesheets and the PVC foam core would improve the shear resistance of the sandwich panels, and the panels with uniaxial shear keys had higher shear strength than the panels with bi-axial shear keys.…”
Section: Introductionmentioning
confidence: 86%